Organoleptic quality of vegetable floss made from papaya and sweet potato - Dwiani, Afe; Rosadi, Narita Amni (Jurnal Agrotek Ummat, 2023)
Meat floss is a food that is usually consumed as a side dish for rice. Currently, floss products are not only made from animal materials but can also use vegetable ingredients such as papaya. Papaya is an ingredient that is widely found as well as sweet potatoes and also the addition of sweet potatoes can improve organoleptic properties. This study aims to determine the organoleptic quality properties of vegetable shredded made from papaya and sweet potato. In this study using a completely randomized design (CRD), namely the formula of papaya and sweet potato, the treatment consisted of B1, namely papaya 30% and sweet potato 70%; B2, papaya 40% and sweet potato 60%; B3, papaya 50% and sweet potato 50%; B4, papaya 60% and sweet potato 40% and B5, papaya 70% and sweet potato 30%. Data analysis using analysis of variance (ANOVA) using Microsoft Excel and SPSS version 16. The organoleptic test results showed that the formula of papaya and sweet potato did not significantly affect the color, texture and taste parameters of both hedonic and scoring tests. Hedonic organoleptic test results of vegetable shredded made from sweet potato and papaya specifications of color, taste and texture with each criterion is like. The results of the vegetable shredded scoring test with the criteria of yellow color, crispy texture and no papaya flavor. Based on the results of hedonic organoleptic tests and scoring, the best/selected treatment is B5 (papaya 70% and sweet potato 30%).